Virtual Model of a Robotic Arm Digital Twin with MuJoCo - Perez Inturias, Bernardo [UNESP] (2024)
In this paper, a digital twin architecture for a Robotis manipulator’s arm is constructed on the Mujoco physics engine SDK. The virtual model in the Mujoco OpenGL virtual environment runs synchronously with the real robot via a TTL-USB physical communication and a C++ script running in Linux. The robot servomotor Dynamixel SDK and the MuJoCo SDK are segregated through threads for parallel execution in the C++ script. From the data flow perspective, we have proposed three scenarios in real-time: Digital Shadow, Digital Driven, and a Digital Twin itself. A preliminary test is performed to confirm the system is functioning as expected. This test compares the motor’s real and virtual torque in a static home position and a digital twin scenario. As this study is to be used as an exemplar for future research on Digital Twin frameworks, we propose future works to continue this research.